Dampak Penghindaran Pajak terhadap Struktur Jatuh Tempo Utang pada UMKM - Eri Kusnanto; Farah Qalbia; Yessica Amelia (Jurnal Visi Manajemen, 2024)
This study aims to review the impact of tax avoidance on the debt maturity structure of Micro, Small, and Medium Enterprises (MSMEs) based on existing literature. Tax avoidance provides MSMEs with the ability to improve short-term cash flow by reducing tax liabilities, which in turn allows for flexibility in managing debt, including extending debt maturity. With increased cash flow, MSMEs tend to rely more on debt as a financing source; however, they also face the risk of higher financing costs due to increased risk perceptions from lenders. The impact of tax avoidance on company reputation can also affect relationships with creditors, potentially leading to higher borrowing costs or difficulties in obtaining debt in the future. Although tax avoidance offers short-term benefits, MSMEs need to consider the potential long-term negative impacts, such as financial risks and reputational damage, when making debt management decisions. This study provides important insights for MSMEs in managing tax avoidance wisely, balancing financial benefits with the potential reputational impact.